2020
DOI: 10.1111/ene.14235
|View full text |Cite
|
Sign up to set email alerts
|

Measuring impulsivity in Parkinson’s disease: a correlational and structural neuroimaging study using different tests

Abstract: Background and purpose Impulsivity is an aspect of personality and a major component of multiple neuropsychiatric conditions. In Parkinson’s disease, it has been associated with the expression of impulse control disorders, a highly prevalent non‐motor complication. Even though multiple tests of impulsivity have been used in this context, the impact of test choice has not been addressed. The aim was to evaluate whether different impulsivity measures in Parkinson’s disease share substantial inter‐scale and anato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…They found that, although the experimental group differed from the control group in self-reported impulsivity and risk behavior, the groups did not differ in DDT scores. In another study with Parkinson's disease patients, no relationships were observed between performance on various tasks that measure risk behavior (BART; IGT) and DDT [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that, although the experimental group differed from the control group in self-reported impulsivity and risk behavior, the groups did not differ in DDT scores. In another study with Parkinson's disease patients, no relationships were observed between performance on various tasks that measure risk behavior (BART; IGT) and DDT [ 125 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impulsivity and risk taking were evaluated by several measures: the Barratt Impulsiveness Scale (BIS11) for impulsivity as a trait, commission errors on the Psychology Experiment Building Language Continuous Performance Task based on the Conners Continuous Performance Test for motor inhibition, the Kirby Delay Discounting Task (DDT) for delay discounting, the Iowa Gambling Task (IGT) for implicit risk with potential losses, the Balloon Analog Risk Task (BART) for implicit risk without losses, and the Game of Dice Task (GDT) for explicit risk 30 . Details on all the impulsivity evaluations except for the GDT are described elsewhere 31 . The GDT is a task inspired by the IGT and the Rogers Risk Task 32 .…”
Section: Methodsmentioning
confidence: 99%
“…30 Details on all the impulsivity evaluations except for the GDT are described elsewhere. 31 The GDT is a task inspired by the IGT and the Rogers Risk Task. 32 It was designed to yield explicit risk choices that remain stable and obvious during the task.…”
Section: Assessmentsmentioning
confidence: 99%
“…Concerning reward learning in PD per se , abnormal BOLD activity was found in the accumbens during reward anticipation when compared to healthy controls [ 245 ] and learning correlated with BOLD activity in this area, which was impaired by dopaminergic treatment [ 246 ]. Morphological studies reported on the one hand that implicit risk was associated with higher gray matter volume [ 247 ], but on the other hand disinhibition was linked to thinning of the accumbens [ 248 ].…”
Section: Regions Of the Limbic Systemmentioning
confidence: 99%